Penerapan Etika Bisnis Islam Terhadap Kegiatan Produksi Pentol Corah dan Otak-Otak Assegaf Jaya Ponorogo - Vita Listiani; Fitra Rizal (Niqosiya: Journal of Economics and Business Research, 2023)
Assegaf Jaya Ponorogo Business is a business engaged in the field of culinary that produces pentol corah and otak-otak typical of Madiun City. Deep Production activities need to pay attention to Islamic production ethics by fulfilling Islamic principles. According to Yusuf Qardhawi, principles in production Islamic is producing in the scope of halal, protection of natural resources, and pay attention to targets. But the facts on the ground are still business people that violates Islamic business ethics towards production activities, such as addition substances that are haram, and there are producers who use tiren meat so that will harm consumers. Consumer losses in the form of material loss, declining health, and loss of consumer trust and loyalty Decreased. The purpose of this study is to analyze the application of activities production of pentol corah and otak-otak in Assegaf Jaya Ponorogo, driving factors and constraints on the application of Islamic business ethics to pentol corah production activities and the brains of Assegaf Jaya Ponorogo, and the impact of implementing production activities pentol corah and otak-otak in Assegaf Jaya Ponorogo. Types of research used is field research using qualitative methods with a descriptive approach. Data collection techniques are carried out by tactics interviews, observations, and documentation. Data sources obtained in the study are: primary data and secondary data. The results of this study show that application of business ethics to the production activities of pentol corah and otak-otak Assegaf Jaya Ponorogo is producing in a halal scope, namely using materials halal standards, do not mix haram, maintain cleanliness and have have a halal certificate from MUI, protection of natural resources with no the existence of production waste that damages the environment, paying attention to targets in the form of the creation of individual self-sufficiency and people's self-sufficiency. Driving factors in the form of A workforce that works according to expertise, sufficient capital, and the use of materials halal standard. Obstacles in the form of scarcity of raw materials for making brains, namely: mackerel and replace it with swordfish. Impact of ethical implementation Islamic business on production activities is a positive impact that can be felt by business owners, labor, and consumers. While the negative impact is in the form of scarcity of raw materials for brain production that affects satisfaction